2022
DOI: 10.1145/3551393
|View full text |Cite
|
Sign up to set email alerts
|

Novice Use of the Java Programming Language

Abstract: Objectives    Java is a popular programming language for use in computing education, but it is difficult to get a wide picture of the issues that it presents for novices, and most studies look only at the types or frequency of errors. In this observational study we aim to learn how novices use different features of the Java language. Participants    Users of the BlueJ development environment have been invited to opt-in to anonymously record their activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…BlueJ is an IDE for Java and Stride primarily used by novices, with a median age of 16. Of their users, 70% are in secondary education and 64% are using it for their first programming experience [4]. The Blackbox dataset has been collecting data from opted-in BlueJ users since 2013 [3].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…BlueJ is an IDE for Java and Stride primarily used by novices, with a median age of 16. Of their users, 70% are in secondary education and 64% are using it for their first programming experience [4]. The Blackbox dataset has been collecting data from opted-in BlueJ users since 2013 [3].…”
Section: Datamentioning
confidence: 99%
“…This was during the COVID-19 pandemic when classes were likely to be virtual, and is two years prior. Previous research [4] has shown that seasonality is a major factor so choosing the same time of year is important, but long-term trends are relatively slow (and no obvious effect of the pandemic on usage was found [4], so choosing 2020 should not be a problem). Another alternative is to pick users in the same time period in 2022 from the 18% of users who have not upgraded their BlueJ version to BlueJ 5.…”
Section: With Vs Without (Rq4)mentioning
confidence: 99%
“…Several studies have investigated the nature of common coding mistakes and quality issues among novice programmers. Several studies [15][16][17][18] provide insights into the frequent types of errors and code quality problems students encounter, including neglect of coding conventions and difficulties with program flow and modularization. These studies collectively underscore the importance of targeted instruction and feedback in helping students overcome these challenges and highlight the potential role of automated tools in educating students about code quality issues.…”
mentioning
confidence: 99%